ANALISA PENGUKURAN LINIER SEBAGAI UPAYA PENGENDALIAN KUALITAS PRODUK DENGAN MENGGUNAKAN METODE CONTROL CHART - Etik Puspitasari (INFO-TEKNIK, 2015)
Quality control should be applied to various fields of both products and services. Quality aims to satisfy and meet customer expectations. One effort in known quality control using control charts, where using these methods we can find products that pass through the specified tolerance limits or defective products.This research was conducted by applying the linear measurement on cylindrical products with a diameter of 20 ± 0.05 mm in turning the results of using calipers with accuracy of 0.05 mm is used to measure the products that have been produced. In this study generated the number of defective products resulting from the process of turning the linear measurement of as much as 6 products that are outside the control limits, which consists of the data no 4, 6, 8, 11, 14 and 22. The factors that cause disability analyzed using fishbone diagrams, and are divided into 4 factors that are of human origin, method, machine and material.Improvement efforts to prevent defective production of turning is necessary to implement training for lathe operators, necessary alignment of straightness of machine or engine. And mechanical drive necessary improvements such as bearings, gears, sliders and then setting up a chisel, setting the workpiece, cutting speed correctly and chisel cutting, selection cutting speed must match the workpiece to be cut and the selection of feeding should be in accordance with the roughness desired , Keywords: Quality control, control charts, linear measurement, fishbone.